Are physically embodied social agents better than disembodied social agents? : the effects of physical embodiment, tactile interaction, and people's loneliness in human–robot interaction - Lee, Kwan Min (2013)
Two experiments were conducted to investigate the effects of physical embodiment in human-agent interaction. Experiment 1 (N = 32) shows positive effects of physical embodiment on the feeling of an agent's social presence, the evaluation of the agent, the assessment of public evaluation of the agent, and the evaluation of the interaction with the agent. A path analysis reveals that the feeling of the agent's social presence mediates the participants' evaluation of the social agent. Experiment 2 (N = 32) shows that physical embodiment with restricted tactile interaction causes null or even negative effects in human agent interaction. In addition, Experiment 2 indicates that lonely people feel higher social presence of social agents, and provide more positive social responses to social agents than non-lonely people. The importance of physical embodiment and tactile communication in human-agent interaction and the diverse role of social robots, especially for the lonely population, are discussed.